Analisis Kinerja Dinas Pemadam Kebakaran Dalam Upaya Pencegahan dan Penanggulangan Bahaya Kebakaran (Studi Kasus Dinas Pemadam Kebakaran dan Penyelamatan Kabupaten Badung) - Listusari, Ni Luh Putu; Yudartha, I Putu Dharmanu; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2018)
ABSTRACT Fire disaster is a disaster that can happen anytime. Many factors cause the fire in the community . In order to reduce fire hazard, the optimal performance of an agency in handling fire problems is needed. Organizational performance is an overall organizational effectiveness for the defined needs of each group and improves the organization's ability to continually achieve its needs effectively. As well as the Fire Department of Badung Regency which tries to deal with the issue of fire with efforts to improve the better performance in the field of disaster prevention and handling. However, in the implementation there are still problems in the organization that resulted in less optimal achievement of the vision of the organization. The purpose of this research is to know the performance of Fire Department of Badung Regency in the effort of prevention and handling fire hazard. This research is descriptive qualitative research. The theory used in this research is performance theory which has six performance measurement indicators: input, process, output, outcome, benefit, impact. Based on the results of the research, the performance of the Fire Department of Badung Regency in the prevention and prevention of fire are still not running optimal. This is because there are still problems faced by Badung Fire Department which is still lack of human resources, lack of firefighting post. Keywords: Analysis, Performance, Organization, Fire Prevention and Respons